Knowledge and perceived barriers for care provision regarding COVID-19 among hospital nurses in Nepal - Adhikari, Bijaya; Mahato, Anju; Acharya, Tara; Kalikote, Bhagawaty (Nepal Medical College Journal, 2023)
COVID-19 pandemic is significantly affecting the overall health and healthcare system globally. It has not shown mercy to Nepal either. All the health facilities are full of COVID-19 patients. Almost all death from COVID-19, has occurred in hospital. Adequate knowledge of nurses regarding the source, transmission, symptoms, and preventive measures of COVID-19 helps to provide effective care and prevent spreading infections from patients to patients, and nurses to patients. Therefore, this study aimed to identify the knowledge regarding COVID-19 and perceived barriers for care provision regarding COVID-19 patients among hospital nurses in Nepal. A cross-sectional descriptive study was conducted in different COVID-19 care designated hospitals of Nepal. Data were collected by using self-administered validated questionnaire through online survey. Descriptive analysis was done by using SPSS-16. More than 80% of nurses had adequate knowledge regarding symptoms, route of transmission, vulnerable population and preventive measures of COVID- 19 and only 15.0% had got training related to COVID-19 pandemic. Nurses perceived negligence of the patients and community people on COVID-19 prevention (84.6%), fear of being infected and carrier to family and community while contacting with patients (80.0%), long duty hour (75.0%), inadequately supply of personal protective equipment and insufficient institutional preparedness (74.0%) were the major barriers for providing care of COVID-19 patients. Thus, hospital authority, nursing administration and nursing professionals’ organizations should play an important role in organizing training to nurses and awareness program to community people. It is also essential in providing required supplies, and facilitates the motivating environment for effective care and prevention of COVID-19.